2020
DOI: 10.1117/1.oe.59.10.102406
|View full text |Cite
|
Sign up to set email alerts
|

Digital holography experiments with degraded temporal coherence

Abstract: To simulate the effects of multiple-longitudinal modes and rapid fluctuations in center frequency, we use sinusoidal phase modulation and linewidth broadening, respectively. These effects allow us to degrade the temporal coherence of our master-oscillator laser, which we then use to conduct digital holography experiments. In turn, our results show that the coherence efficiency decreases quadratically with fringe visibility and that our measurements agree with our models to within 1.8% for sinusoidal phase modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…We do so at various FPA integration times and path-length differences between the signal and reference. Like in the previous experiments [10], [11], these efficiencies contribute to the overall mixing efficiency. New to this paper, however, is the fact that both the vibration efficiency and the coherence efficiency depend on the FPA integration time.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…We do so at various FPA integration times and path-length differences between the signal and reference. Like in the previous experiments [10], [11], these efficiencies contribute to the overall mixing efficiency. New to this paper, however, is the fact that both the vibration efficiency and the coherence efficiency depend on the FPA integration time.…”
supporting
confidence: 66%
“…In further experiments, we investigated the multiplicative losses due to coherence [11]. These experiments were significant because our results showed that the coherence efficiency, which is another efficiency that makes up the overall mixing efficiency, decreases quadratically with fringe visibility and that our measurements agreed well with our models.…”
supporting
confidence: 63%
See 3 more Smart Citations